Measuring Radicalism in International Relations: an Analysis and Interpretation in West Sulawesi - Wandi Abbas; Andi Ismira; Zainuddin Losi (PT Mattawang Mediatama Solution, 2024)
The dynamics of social life in Indonesia are increasingly developing along with developments in the order of life which have a direct impact on relations between communities and the relationship between society and government. The development of information technology and the unavoidable level of globalization are accelerating the pace of change in social movements, which were previously just ordinary movements, into organized social movements in the economic, political, social, and religious fields. This research uses qualitative methods that focus on in-depth interviews and library research as support. The birth of social movements is the impact of democratic principles which provide space and opportunities for people to fight for constitutional rights. The development of information technology on social movements needs to receive government attention, even though social movements are part of the principles of constitutional democracy. It is feared that social movements that are not paid attention to by the government in the current era of globalization will be influenced by radicalism which threatens the stability of the government, including in West Sulawesi Province, which is not impossible if social movements in the form of radicalism movements also develop rapidly. Using the soul approach will certainly be a way to suppress the actions of radicalism movements in West Sulawesi